Laminate and method for producing same
By forming a metal-based particle aggregate layer on the base material of the laminated body and covering the silicon-containing atom layer, combined with the heat treatment process, the problem of insufficient resistance to cleaning of the existing laminated body to the piranha solution is solved, and a high resistance laminated body structure is realized.
Patent Information
- Application Number
- CN202380060701.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing laminates need to undergo subsequent processes such as surface modification before cleaning the piranha solution, and the resistance to cleaning the piranha solution is insufficient.
A laminated body consisting of a metal-based particle aggregate layer and a silicon-containing atom-containing layer is used to form a metal-based particle aggregate layer on a substrate and cover it with a silicon-containing atom-containing layer, and then heat treatment is performed to improve the resistance of the laminated body.
Excellent resistance to cleaning of piranha solution is achieved, and the surface damage and structural changes of the laminated body are avoided during the cleaning process.
Smart Images

Figure CN119731021A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate including a metal-based particle assembly layer and a method for producing the laminate. Background Art
[0002] A technique for enhancing fluorescence by utilizing localized plasmon resonance of metal nanoparticles is known (e.g., Patent Document 1). Patent Document 1 describes a scheme for using a laminate including an island layer (2) composed of a plurality of metal particles and a spacer layer (5) covering the island layer for a photochemical fluorescence sensor.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 08-271431 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] The laminated body as described above is sometimes cleaned with a piranha solution before subsequent processes such as surface modification. The object of the present invention is to provide a laminated body including a metal-based particle assembly layer composed of a plurality of metal-based particles and having excellent resistance to piranha solution cleaning and a method for producing the laminated body.
[0008] Solutions for solving problems
[0009] The present invention provides the following laminated body and a method for producing the same.
[0010] [1] A laminate comprising: a metal-based particle assembly layer composed of a plurality of metal-based particles arranged separately from each other; and a silicon-containing atom layer,
[0011] The silicon-atom-containing layer has a first surface.
[0012] The signal intensity of carbon atoms on the first surface measured by X-ray photoelectron spectroscopy is 20.0 atomic % or less.
[0013] [2] The laminate according to [1], comprising: a substrate; the metal-based particle assembly layer disposed on a surface of the substrate; and the silicon-containing atom layer disposed on the metal-based particle assembly layer.
[0014] The silicon atom-containing layer is disposed so as to cover the entire surface of the metal-based particle assembly layer on the side opposite to the substrate.
[0015] [3] The laminate according to [1] or [2], wherein the silicon atom-containing layer is an amorphous layer.
[0016] [4] The laminate according to any one of [1] to [3], wherein the silicon atom-containing layer is a wet coating layer.
[0017] [5] The laminate according to any one of [1] to [4], wherein the average thickness of the silicon atom-containing layer is 10 nm to 300 nm.
[0018] [6] The laminate according to any one of [1] to [5], wherein the metal-based particles are made of silver.
[0019] [7] The laminate according to any one of [1] to [6], wherein the average particle size of the plurality of metal-based particles is within a range of 200 nm to 1600 nm, the average height is within a range of 55 nm to 500 nm, and the aspect ratio defined by the ratio of the average particle size to the average height is within a range of 1 to 8.
[0020] In the metal-based particle assembly layer, the plurality of metal-based particles are arranged such that an average distance between each of the metal-based particles adjacent thereto is within a range of 1 nm to 150 nm.
[0021] [8] The laminate according to [7], wherein the aspect ratio is greater than 1.
[0022] [9] The laminate according to any one of [1] to [8], wherein the first surface has an arithmetic mean roughness Ra of 10 nm or less as measured in accordance with JIS B 0601:2001.
[0023]
[10] A laminate according to any one of [1] to [9], wherein the arithmetic mean roughness Ra of the first surface measured in accordance with JIS B 0601:2001 after being immersed in a mixed solution of 98% by mass concentrated sulfuric acid and 30% by mass hydrogen peroxide solution at a volume ratio of 4:1 at a temperature of 25°C for 30 minutes is 15 nm or less.
[0024]
[11] A method for producing a laminated body,
[0025] The laminate comprises: a metal-based particle assembly layer composed of a plurality of metal-based particles arranged separately from each other; and a silicon-containing atom layer.
[0026] The silicon-atom-containing layer has a first surface.
[0027] The signal intensity of carbon atoms on the first surface measured by X-ray photoelectron spectroscopy is 20.0 atomic % or less,
[0028] The aforementioned manufacturing method comprises the following steps:
[0029] forming the metal-based particle assembly layer on a substrate;
[0030] A step of coating a silicon atom-containing layer-forming composition on a substrate having the metal-based particle assembly layer formed thereon to form a coating layer; and
[0031] A step of heat-treating the coating layer at a temperature of 300° C. to 800° C.
[0032]
[12] The production method according to
[11] , further comprising a step of degreasing and cleaning the substrate before the step of forming the metal-based particle assembly layer.
[0033] Effects of the Invention
[0034] It is possible to provide a laminate including a metal-based particle assembly layer composed of a plurality of metal-based particles and having excellent resistance to piranha solution cleaning, and a method for producing the laminate. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a cross-sectional view schematically showing an example of the laminated body of the present invention.
[0036] Figure 2 These are SEM images of the metal-based particle assembly layer obtained in Example 1 observed from directly above (10,000-fold and 50,000-fold scales).
[0037] Figure 3 This is an AFM image of the metal-based particle assembly layer obtained in Example 1.
[0038] Figure 4 This is a SEM image (50,000-fold scale) of the laminate of Example 1 observed from the silicon-atom-containing layer side before the piranha solution cleaning test.
[0039] Figure 5 This is a SEM image (50,000-fold scale) of the laminate of Example 1 after the piranha solution cleaning test when observed from the silicon atom-containing layer side.
[0040] Figure 6 This is an optical microscope photograph (700-fold scale) of the laminate of Example 1 before the piranha solution cleaning test when observed from the silicon atom-containing layer side.
[0041] Figure 7 This is an optical microscope photograph (700-fold scale) of the laminate of Example 1 after the piranha solution cleaning test when observed from the silicon atom-containing layer side.
[0042] Figure 8 This is an optical microscope photograph (magnitude 700) of the laminate of Example 2 after the piranha solution cleaning test when observed from the silicon atom-containing layer side.
[0043] Fig. 9 This is an optical microscope photograph (700-fold scale) of the laminate of Example 3 after the piranha solution cleaning test when observed from the silicon atom-containing layer side.
[0044] Fig.10 This is an optical microscope photograph (700-fold scale) of the laminate of Comparative Example 1 after the piranha solution cleaning test when observed from the silicon atom-containing layer side. DETAILED DESCRIPTION
[0045] <Laminated body>
[0046] (1) Summary
[0047] The stack of the present invention (hereinafter also referred to as "stack") is a stack comprising: a metal-based particle assembly layer composed of a plurality of metal-based particles arranged separately from each other; and a silicon-containing atom layer, the silicon-containing atom layer having a first surface, and the signal intensity of carbon atoms on the first surface measured by X-ray photoelectron spectroscopy is less than 20.0 atomic %.
[0048] Figure 1 It is a cross-sectional view schematically showing an example of a laminated body. Figure 1 The laminate shown includes: a substrate 10; a metal-based particle assembly layer 20 disposed on the surface of the substrate 10; and a silicon-containing atom layer 30 disposed on the metal-based particle assembly layer 20. The metal-based particle assembly layer 20 is an assembly of a plurality of metal-based particles 21, and is a layer composed of a plurality of metal-based particles 21 disposed separately from each other. The silicon-containing atom layer 30 has a first surface 31, and the signal intensity of carbon atoms on the first surface 31 measured by X-ray photoelectron spectroscopy is 20.0 atomic % or less.
[0049] According to the present invention, since the silicon-containing atom layer having the first surface with a signal intensity of carbon atoms of 20.0 atomic % or less is stacked, a stack having excellent resistance to piranha solution cleaning can be provided. The stack can be used, for example, for sensor elements, etc. A suitable example of a sensor element is a biosensor element.
[0050] It should be noted that the laminate may have layers other than the substrate 10, the metal-based particle assembly layer 20 and the silicon-containing atom layer 30. Examples of such layers include layers interposed between the metal-based particle assembly layer 20 and the silicon-containing atom layer 30 and layers laminated on the silicon-containing atom layer 30.
[0051] (2) Metallic particle assembly layer
[0052] The metal-based particle assembly layer 20 is a layer composed of a plurality of metal-based particles 21 arranged separately from each other, and is preferably a plasma structure. "Plasma structure" refers to a structure that can show localized plasma resonance. Plasma refers to a compression wave of free electrons generated by the vibration of free electron groups in the structure. By making the metal-based particle assembly layer 20 a plasma structure, the intensity of the luminescence (fluorescence, etc.) from the luminophore that marks the substance to be detected can be enhanced, for example, when the laminate is used in a sensor element. Therefore, the laminate can be suitable for use as a luminescence enhancement element for various sensor elements. By using the laminate in a sensor element, the sensitivity, quantitative accuracy and / or reproducibility (stability) of the sensor element can be improved.
[0053] The metal-based particle assembly layer 20 preferably satisfies the following conditions.
[0054] The multiple metal-based particles 21 constituting the metal-based particle assembly layer 20 are as follows: the average particle size is within the range of greater than 200nm and less than 1600nm, the average height is within the range of greater than 55nm and less than 500nm, and the aspect ratio defined by the ratio of the average particle size to the average height is within the range of greater than 1 and less than 8. In the metal-based particle assembly layer 20, the multiple metal-based particles 21 are arranged in such a manner that the average distance between the adjacent metal-based particles is within the range of greater than 1nm and less than 150nm.
[0055] The metal-based particle assembly layer 20 having the structure satisfying the above-mentioned requirements and the laminated body having the same can show the following characteristics [a] and [b]. These characteristics are considered to be manifested by the interaction between the localized plasmas shown by the plurality of metal-based particles 21 constituting the metal-based particle assembly layer 20.
[0056] [a] The range of action of the plasmon resonance shown in the metal-based particle assembly layer 20 is wide. As a result, for example, the range of the plasmon-based luminescence enhancement effect can be expanded, and thus, the luminescence of the luminescent body located within a range of, for example, several hundred nanometers (e.g., 200 nanometers) from the surface of the metal-based particle assembly layer 20 can also be enhanced.
[0057] [b] The metal-based particle assembly layer 20 exhibits strong plasmon resonance, thereby, for example, achieving a strong light emission enhancement effect.
[0058] Regarding the above [a], according to the laminate of the present invention, the luminescence of the luminescent body arranged at a position separated from the metal-based particle assembly layer 20 by, for example, more than 10 nm, further tens of nm (for example, 20 nm, 30 nm or 40 nm), further more than 100 nm or more than 200 nm can be enhanced. Regarding the above [b], the intensity of the plasma resonance shown by the laminate is not the simple sum of the localized plasma resonance shown by each metal-based particle at a specific wavelength but an intensity greater than that. In the laminate, each metal-based particle interacts with each other and exhibits a strong plasma resonance. It is believed that this strong plasma resonance is manifested by the interaction between the localized plasmas of the metal-based particles.
[0059] Generally, for a plasma structure, when the absorption spectrum is measured by spectrophotometry, a plasma resonance peak is observed as a peak located on the longest wavelength side in the ultraviolet to visible region (hereinafter also referred to as a "plasma peak"). The intensity of the plasma resonance of the plasma structure can be evaluated by the magnitude of the absorbance at the maximum wavelength of the plasma peak. There is a tendency that the intensity of the plasma resonance increases as the absorbance value increases. For the metal-based particle assembly layer 20 having the structure specified above, when the absorption spectrum is measured by the following spectrophotometry, the absorbance at the maximum wavelength of the plasma peak located on the longest wavelength side in the ultraviolet to visible region can be greater than 1, further can be greater than 1.5, and further can be about 2.
[0060] The absorption spectrum of the plasma structure can be measured by spectrophotometry. Specifically, the absorption spectrum is obtained as follows: the intensity of the transmitted light I and the intensity of the transmitted light I0 are measured respectively by using an integrating sphere spectrophotometer, wherein the intensity of the transmitted light I is the intensity of the transmitted light in all directions transmitted to the side of the metal-based particle assembly layer by irradiating the incident light in the ultraviolet to visible light region from the back side of the glass substrate stacked with the metal-based particle assembly layer (the opposite side to the metal-based particle assembly layer) and perpendicular to the substrate surface, and the intensity of the transmitted light I0 is the intensity of the transmitted light in all directions transmitted from the opposite side of the incident surface by irradiating the same incident light as above from a substrate with the same thickness and the same material as the substrate of the measured sample and perpendicular to the surface of the substrate without the metal-based particle assembly layer. At this time, the absorbance as the vertical axis of the absorption spectrum is expressed by the following formula:
[0061] Absorbance = -log 10 (I / I0).
[0062] The absorption spectrum can be measured using a general spectrophotometer.
[0063] When measuring the maximum wavelength of the plasmon peak located on the longest wavelength side in the ultraviolet to visible light region and its absorbance, the absorption spectrum can be measured by narrowing the measurement field using an objective lens and a spectrophotometer.
[0064] In order to form a plasmon structure in the metal-based particle assembly layer 20, the metal-based particles 21 are preferably composed of a material capable of plasmon resonance in the ultraviolet to visible light region. The material capable of plasmon resonance in the ultraviolet to visible light region refers to a material that shows a plasmon peak in the ultraviolet to visible light region in the absorption spectrum measurement based on spectrophotometry when forming nanoparticles or their aggregates.
[0065] Examples of metal materials capable of plasmon resonance in the ultraviolet to visible region include: noble metals such as gold, silver, copper, platinum, and palladium; metals other than noble metals such as aluminum and tantalum; alloys containing a metal selected from the noble metal and metals other than noble metals; and metal compounds (metal oxides, metal salts, etc.) containing a metal selected from the noble metal and metals other than noble metals. Among them, as metal materials capable of plasmon resonance in the ultraviolet to visible region, noble metals such as gold, silver, copper, platinum, and palladium are preferred, and silver is more preferred from the viewpoint of being inexpensive and having low absorption (small imaginary part of dielectric function in visible wavelength).
[0066] From the viewpoint of effectively obtaining the effects of [a] and [b] described above, the average particle size of the plurality of metal-based particles 21 constituting the metal-based particle assembly layer 20 is preferably within a range of 200 nm to 1600 nm, more preferably 200 nm to 1200 nm, further preferably 250 nm to 500 nm, and further preferably 300 nm to 500 nm. The average particle size of the metal-based particles 21 is preferably appropriately selected depending on the type of metal-based material constituting the metal-based particles 21.
[0067] The average particle size of the plurality of metal-based particles 21 is the average particle size of the 10 selected metal-based particles when 10 metal-based particles are randomly selected from the SEM observation image directly above the metal-based particle assembly layer 20 composed of the plurality of metal-based particles 21, 5 tangent diameters are randomly drawn in each metal-based particle image (wherein, all straight lines that become tangent diameters can pass only through the inside of the metal-based particle image, and one straight line that passes only through the inside of the metal-based particle is recorded as the longest straight line drawn), and the average value (hereinafter, this average value is also referred to as the "tangent diameter average value") is used as the particle size of each metal-based particle. The tangent diameter is defined as the perpendicular line connecting the interval when the outline (projection image) of the metal-based particle is sandwiched by two parallel lines connected to it (Nikkan Kogyo Shimbun, "Particle Measurement Technology", 1994, page 5).
[0068] When describing the method for measuring the average particle size in more detail, first, a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd. or an equivalent device is used to measure the SEM observation image. Next, the observation image obtained is read with 1280 pixels horizontally and 960 pixels vertically using the free image processing software "ImageJ" manufactured by the National Institutes of Health of the United States. Then, the random number generation function "RANDBETWEEN" of the spreadsheet software "Excel" manufactured by Microsoft Corporation is used to obtain 10 random numbers (x1, x2, x3, x4, x5, x6, x7, x8, x9, x10, x11, x12, x13, x14, x15, x16, x17, x18, x19, x20, x21, x22, x23, x24, x25, x26, x27, x28, x29, x30, x31, x32, x33, x34, x35, x36, x37, x38, x39, x40, x41, x42, x43, x44, x45, x46, x47, x48, x49, x50, x51, x52, x53, x54, x55, x56, x57, x58, x59, x60, x61, x62, x63, x64, x65 10 ), get 10 random numbers from 1 to 960 (y1, y2, y3, y4, y5, y6, y7, y8, y9, y 10 ). From the 10 random numbers obtained, 10 groups of random number combinations (x1, y1), (x2, y2), (x3, y3), (x4, y4), (x5, y5), (x6, y6), (x7, y7), (x8, y8), (x9, y9) and (x 10 ,y 10 ). Using the random number values generated from 1 to 1280 as the x-coordinate and the random number values generated from 1 to 960 as the y-coordinate, we get 10 sets of coordinate points (x1, y1), (x2, y2), (x3, y3), (x4, y4), (x5, y5), (x6, y6), (x7, y7), (x8, y8), (x9, y9) and (x 10 ,y 10 ). Then, for a total of 10 metal-based particle images including the coordinate point, the above-mentioned tangent diameter average values are obtained respectively, and then the average particle diameter is obtained as the average value of the 10 tangent diameter average values. In the case where at least any one of the 10 coordinate points of the 10 groups of random number combinations is not included in the metal-based particle image, or in the case where two or more coordinate points are included in the same metal-based particle, the random number combination is abolished, and random number generation is repeated until all 10 coordinate points are included in different metal-based particle images.
[0069] In order to effectively obtain the effects of [a] and [b], the average height of the plurality of metal-based particles 21 is preferably within a range of 55 nm to 500 nm, more preferably 55 nm to 300 nm, and even more preferably 70 nm to 150 nm. The average height of the metal-based particles 21 refers to the average value of 10 measured values obtained by randomly selecting 10 metal-based particles in the AFM observation image of the metal-based particle assembly layer 20 and measuring the heights of the 10 metal-based particles.
[0070] For the plurality of metal-based particles 21, from the viewpoint of effectively obtaining the effects of [a] and [b], the aspect ratio is preferably within the range of 1 or more and 8 or less, more preferably 2 or more and 8 or less, and further preferably 2.5 or more and 8 or less. The aspect ratio of the metal-based particles 21 is defined by the ratio of the average particle diameter to the average height (average particle diameter / average height). The metal-based particles 21 may be spherical, but from the viewpoint of effectively obtaining the effects of [a] and [b], they preferably have a flat shape with an aspect ratio greater than 1.
[0071] From the viewpoint of effectively obtaining the effects of [a] and [b] described above, the plurality of metal-based particles 21 in the metal-based particle assembly layer 20 are preferably arranged so that the average distance between each of the metal-based particles adjacent thereto (hereinafter also referred to as "average inter-particle distance") is within a range of 1 nm or more and 150 nm or less. By arranging the plurality of metal-based particles 21 at such an average inter-particle distance, strong plasmon resonance can be easily obtained, and the effect of extending the range of action of plasmon resonance can be further enhanced.
[0072] The average inter-particle distance is more preferably 1 nm to 100 nm, more preferably 1 nm to 50 nm, and even more preferably 1 nm to 20 nm, from the viewpoint of effectively obtaining the effects of [a] and [b] above. If the average inter-particle distance is less than 1 nm, electron migration based on the Dexter mechanism occurs between particles, which is disadvantageous in terms of deactivation of localized plasma.
[0073] The average inter-particle distance refers to the average value of the inter-particle distances of 10 metal-based particles randomly selected from the SEM observation image directly above the metal-based particle assembly layer 20 composed of a plurality of metal-based particles 21, when the inter-particle distances of the 10 metal-based particles are calculated for each of the selected metal-based particles. The inter-particle distances of the adjacent metal-based particles refer to the value obtained by measuring the distances of all the adjacent metal-based particles (the minimum distance between the surfaces of the adjacent metal-based particles) and averaging them.
[0074] When describing the method for measuring the average interparticle distance in more detail, first, a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd. or an equivalent device is used to measure the SEM observation image. Next, the observation image obtained is read with 1280 pixels horizontally and 960 pixels vertically using the free image processing software "ImageJ" manufactured by the National Institutes of Health of the United States. Then, the random number generation function "RANDBETWEEN" of the spreadsheet software "Excel" manufactured by Microsoft Corporation is used to obtain 10 random numbers (x1 to x2) from 1 to 1280, respectively. 10 ), get 10 random numbers (y1~y 10 ). From the 10 random numbers obtained, 10 groups of random number combinations (x1, y1) to (x 10 ,y 10 ). The random number values generated from 1 to 1280 are used as the x-coordinates, and the random number values generated from 1 to 960 are used as the y-coordinates, and 10 sets of coordinate points (x1, y1) to (x 10 ,y 10 ). Then, for a total of 10 metal-based particle images including the coordinate point, the inter-particle distances between the metal-based particle and the adjacent metal-based particles are obtained respectively, and then, the average inter-particle distance is obtained as the average value of the inter-particle distances between the 10 adjacent metal-based particles. In the case where at least any one of the 10 coordinate points of the 10 groups of random number combinations is not included in the metal-based particle image, or in the case where two or more coordinate points are included in the same metal-based particle, the random number combination is abolished, and random number generation is repeated until all 10 coordinate points are included in different metal-based particle images.
[0075] From the viewpoint of effectively obtaining the effects of [a] and [b] described above, the plurality of metal-based particles 21 in the metal-based particle assembly layer 20 are preferably arranged so that the standard deviation of the average inter-particle distance is 35 nm or less. From the viewpoint of effectively obtaining the effects of [a] and [b] described above, the standard deviation of the average inter-particle distance is more preferably 30 nm or less, and is preferably 0.1 nm or more, more preferably 0.2 nm or more, and even more preferably 0.3 nm or more.
[0076] The standard deviation of the average inter-particle distance is defined as follows. From the SEM observation image directly above the metal-based particle assembly layer 20 composed of multiple metal-based particles 21, first randomly select one metal-based particle, and for this metal-based particle, find the inter-particle distance with the adjacent metal-based particles. The inter-particle distance with the adjacent metal-based particles refers to: measuring all the distances with the adjacent metal-based particles (the minimum distance between the surfaces) separately, and averaging them to obtain the value. In the above SEM observation image, 9 metal-based particles different from the above one are randomly selected, and for these 9 metal-based particles, the inter-particle distance with the adjacent metal-based particles is calculated in the same manner as above. The standard deviation of the inter-particle distance with the adjacent metal-based particles for a total of 10 metal-based particles obtained in this way is defined as the standard deviation of the average inter-particle distance.
[0077] When describing the method for measuring the standard deviation of the average inter-particle distance in more detail, first, a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd. or an equivalent device is used to measure the SEM observation image. Next, the observation image obtained is read with 1280 pixels horizontally and 960 pixels vertically using the free image processing software "ImageJ" manufactured by the National Institutes of Health of the United States. Then, the random number generation function "RANDBETWEEN" of the spreadsheet software "Excel" manufactured by Microsoft Corporation is used to obtain 10 random numbers (x1 to x2) from 1 to 1280, respectively. 10 ), get 10 random numbers (y1~y 10 ). From the 10 random numbers obtained, 10 groups of random number combinations (x1, y1) to (x 10 ,y 10 ). The random number values generated from 1 to 1280 are used as the x-coordinates, and the random number values generated from 1 to 960 are used as the y-coordinates, and 10 sets of coordinate points (x1, y1) to (x 10 ,y 10 ). Then, for a total of 10 metal-based particle images including the coordinate point, the inter-particle distances between the metal-based particle and the adjacent metal-based particles are obtained respectively, and then, as the standard deviation of the inter-particle distances between the 10 adjacent metal-based particles, the standard deviation of the average inter-particle distance is obtained. In the case where at least any one of the 10 coordinate points of the 10 groups of random number combinations is not included in the metal-based particle image, or in the case where two or more coordinate points are included in the same metal-based particle, the random number combination is abolished, and random number generation is repeated until all 10 coordinate points are included in different metal-based particle images.
[0078] For the metal-based particles 21, from the perspective of efficiently exciting plasma, it is preferred that the surface thereof be formed by a smooth curved surface, and it is particularly preferred that the surface be a flat shape formed by a smooth curved surface. However, the surface may also contain some tiny bumps (roughness). In this sense, the metal-based particles may also be irregular.
[0079] The number of metal-based particles 21 contained in the metal-based particle assembly layer 20 is usually 10 or more, preferably 30 or more. By forming a metal-based particle assembly layer containing 10 or more metal-based particles, it is easy to manifest strong plasma resonance and extension of the range of action of plasma resonance by utilizing the interaction between the localized plasmas of the metal-based particles. The number of metal-based particles 21 contained in the metal-based particle assembly layer 20 can be, for example, 50 or more, further 1,000 or more, and further 10,000 or more. The number density of the metal-based particles 21 in the metal-based particle assembly layer 20 is preferably 7 particles / μm 2 More preferably, 15 pieces / μm 2 above.
[0080] The metal-based particle assembly layer 20 preferably does not show conductivity as the layer, and the metal-based particles 21 constituting the metal-based particle assembly layer 20 are each more preferably non-conductive between the metal-based particles adjacent thereto. In the metal-based particle assembly layer 20, when there are sites where electron transfer can be performed between the metal-based particles 21, there is a tendency for the plasma resonance effect to decrease. Therefore, it is preferred that the metal-based particles 21 are reliably separated, and no conductive material is interposed between the metal-based particles 21. The metal-based particles 21 themselves may also have conductivity.
[0081] In the case where the metal-based particle assembly layer 20 does not show conductivity as a layer, for example, when a pair of tester probes of a multimeter [tester ("E2378A" manufactured by Hewlett-Packard Development Company, LP)] are brought into contact with the metal-based particle assembly layer 20 with a deviation of 10 mm to 15 mm, and the range is set to "30 MΩ", the resistance value under this measurement condition is greater than 30 MΩ, and the result can be confirmed by being displayed as "overload".
[0082] (3) Method for producing metal-based particle assembly layer
[0083] The metal-based particle assembly layer 20 can be produced, for example, by the following method.
[0084] [A] A bottom-up method in which a plurality of metal-based particles 21 are grown from tiny seeds on a substrate 10;
[0085] [B] A method of covering the plurality of metal particles 21 with a protective film formed of an amphiphilic material having a predetermined thickness and then forming the protective film on the substrate 10 by an LB (Langmuir Blodgett) film method;
[0086] [C] In addition, a method of post-treating a thin film produced by vapor deposition or sputtering; a resist process; an etching process; a casting method using a dispersion liquid in which metal-based particles are dispersed; etc.
[0087] The above method [A] preferably includes a step of growing metal-based particles on a substrate 10 adjusted to a predetermined temperature at an extremely low speed (hereinafter also referred to as a "particle growth step"). According to the manufacturing method including the above particle growth step, a metal-based particle assembly layer 20 having the above-mentioned preferred average particle size, average height, aspect ratio, average inter-particle distance, and standard deviation of the average inter-particle distance can be obtained with good control.
[0088] In the particle growth step, the speed at which the metal-based particles grow on the substrate 10 is preferably less than 1 nm / minute, more preferably less than 0.5 nm / minute, in terms of the average height growth rate. The average height growth rate here may also be referred to as the average deposition rate or the average thickness growth rate of the metal-based particles, and is defined by the following formula:
[0089] Average height of metal-based particles / growth time of metal-based particles.
[0090] The definition of "average height of metal-based particles" is as described above.
[0091] The metal-based particle growth time refers to the time from the start to the end of the growth of the metal-based particles, specifically, the supply time of the metal-based material. When the metal-based particle assembly layer 20 is regarded as a film, the metal-based particle growth time can also be referred to as the film formation time. When the method for growing the metal-based particles is sputtering, the metal-based particle growth time is the sputtering time.
[0092] The temperature of the substrate 10 in the particle growth step is preferably 100°C to 450°C, more preferably 200°C to 450°C, further preferably 250°C to 350°C, further preferably 300°C or thereabouts (about 300°C±10°C).
[0093] By adjusting the average height growth rate, substrate temperature and / or metal-based particle growth time, the average inter-particle distance and its standard deviation, average particle size, average height, and aspect ratio of the plurality of metal-based particles 21 grown on the substrate 10 can be controlled.
[0094] The pressure (pressure in the chamber of the device) when the metal-based particles are grown is not particularly limited as long as it is a pressure that can cause the particles to grow, and is usually lower than atmospheric pressure. The lower limit of the pressure is not particularly limited, but is preferably 0.5 Pa or more, more preferably 6 Pa or more, and further preferably 10 Pa or more in order to easily adjust the average height growth rate to the above range.
[0095] The specific method for growing the metal-based particles on the substrate 10 is not particularly limited as long as it is a method that can grow the particles at an average height growth rate of less than 1 nm / minute, and examples thereof include sputtering, vacuum evaporation and other evaporation methods. Among the sputtering methods, direct current (DC) sputtering is preferably used because it can relatively easily grow a metal-based particle assembly layer and can easily maintain an average height growth rate of less than 1 nm / minute.
[0096] There is no particular limitation on the sputtering method, and the following can be used: a DC argon ion sputtering method in which argon ions generated by an ion gun or plasma discharge are accelerated in an electric field and irradiated onto a target material. Other conditions such as the current value, voltage value, and substrate / target distance in the sputtering method are appropriately adjusted so that particles grow at an average height growth rate of less than 1 nm / minute.
[0097] It should be noted that in order to obtain the metal-based particle assembly layer 20 having the above-mentioned preferred average particle size, average height, aspect ratio, average inter-particle distance and standard deviation of the average inter-particle distance under good control, it is preferred that in addition to making the average height growth rate lower than 1 nm / minute in the particle growth process, the average particle size growth rate is also lower than 5 nm, but when the average height growth rate is lower than 1 nm / minute, the average particle size growth rate is usually lower than 5 nm. The average particle size growth rate is more preferably less than 1 nm / minute. The average particle size growth rate is defined by the following formula:
[0098] Average particle size of metal-based particles / growth time of metal-based particles.
[0099] The definitions of "average particle size of metal-based particles" and "growth time of metal-based particles" are as described above.
[0100] In order to obtain a metal-based particle assembly layer 20 having the above-mentioned preferred average particle size, average height, aspect ratio, average inter-particle distance and standard deviation of the average inter-particle distance, it is preferred to appropriately adjust the metal-based particle growth time in the particle growth process while considering the above-mentioned preferred manufacturing conditions.
[0101] (4) Base material
[0102] The substrate 10 is preferably formed of a non-conductive material. This is because, when the substrate 10 is formed of a conductive material, electron transfer can be performed between the metal particles formed thereon, and therefore, there is a tendency for the plasma resonance effect to be reduced. As non-conductive materials constituting the substrate 10, inorganic insulating materials such as mica, SiO2, ZrO2, and glass, thermoplastic resins, etc. can be cited. In the laminate having the substrate 10, the metal particle assembly layer 20 is preferably directly laminated on the substrate 10.
[0103] The substrate 10 may be a single-layer structure or a multi-layer structure. The shape of the substrate 10 may be, for example, a plate-like shape, but may also be a shape having a curved surface (e.g., a granular shape). The plate-like substrate 10 (substrate) preferably has a smooth surface, but may have a surface concave-convexity or a curved surface. The substrate 10 may be a light-transmitting or optically transparent substrate, or may be non-light-transmitting (light-absorbing).
[0104] The thickness of the substrate 10 is not particularly limited, and is, for example, 10 μm to 10 mm, preferably 20 μm to 5 mm, and more preferably 30 μm to 1 mm.
[0105] (5) Silicon atomic layer
[0106] The silicon atom-containing layer 30 of the stacked body is a layer having a first surface. The first surface here refers to at least a portion of the surface defining the outer edge of the silicon atom-containing layer 30, and in the stacked body including the substrate 10, preferably refers to at least a portion of the surface on the side opposite to the substrate 10 side.
[0107] Figure 1 In the example of the stacked body shown, the silicon-atom-containing layer 30 is arranged on the opposite side of the substrate 10 with respect to the metal-based particle assembly layer 20, and is arranged in a manner that covers the entire surface of the metal-based particle assembly layer 20 on the side opposite to the substrate 10. Thus, from the viewpoint of protecting the metal-based particle assembly layer 20, etc., the silicon-atom-containing layer 30 is preferably arranged in a manner that covers the entire surface of the metal-based particle assembly layer 20 on the side opposite to the substrate 10, that is, a portion of the surface on the side opposite to the substrate 10 in the stacked body is not constituted by the surface of the metal-based particle assembly layer 20. Figure 1 The surface of the silicon atom-containing layer 30 of the stacked body opposite to the substrate 10 side is the first surface 31, and the surface of the stacked body opposite to the substrate 10 is entirely composed of the surface (first surface) of the silicon atom-containing layer 30. In addition, the silicon atom-containing layer 30 is preferably formed in a manner that fills the gaps between the metal-based particles 21.
[0108] The signal intensity of carbon atoms measured by X-ray photoelectron spectroscopy of the first surface 31 of the silicon atom-containing layer 30 is 20.0 atomic % or less. Thus, the laminate can have excellent resistance to piranha solution cleaning. From the viewpoint of improving the resistance, the signal intensity of carbon atoms is preferably 18.0 atomic % or less, more preferably 15.0 atomic % or less, further preferably 12.0 atomic % or less, and further preferably 10.0 atomic % or less.
[0109] The signal intensity of the carbon atoms is preferably 0.2 atomic % or more, more preferably 0.5 atomic % or more, further preferably 1 atomic % or more, and can be 5 atomic % or more. In the case of forming the silicon-containing atom layer 30 having too low a signal intensity of the carbon atoms, there is a concern about damaging the metal-based particle assembly layer 20 during its formation process in the selection of the formation process. Specifically, for example, there is a concern that a process of oxygen introduction and heating at a level that may cause concern about damaging the metal-based particle assembly layer 20 may have to be adopted. In addition, in the case of forming the silicon-containing atom layer 30 having not too low a signal intensity of the carbon atoms, a composition having a relatively high signal intensity of the carbon atoms can be used as the composition for forming the silicon-containing atom layer described later. By using such a composition to form the silicon-containing atom layer 30, the coating properties of the composition and the mass productivity of the stack can be improved, and the smoothness of the surface (the surface on the opposite side of the substrate 10, the first surface) of the silicon-containing atom layer 30 can be improved.
[0110] The signal intensity of the carbon atoms on the first surface can be measured by X-ray photoelectron spectroscopy according to the conditions described in the [Example] described later. The signal intensity of the carbon atoms is defined as the ratio (%) of the area occupied by the signal of the carbon atoms in the spectrum obtained by X-ray photoelectron spectroscopy to the total area of all signals.
[0111] For the surface on the opposite side of the laminate to the substrate 10, the signal intensity of the metal atoms constituting the metal-based particles 21 measured by X-ray photoelectron spectroscopy is preferably 7.0 atomic % or less, more preferably 5.0 atomic % or less, further preferably 3.0 atomic % or less, further preferably 2.0 atomic % or less, particularly preferably 1.5 atomic % or less, further particularly preferably 1.0 atomic % or less, further particularly preferably 0.7 atomic % or less, and most preferably below the detection limit. In this way, the metal-based particle assembly layer 20 can be more reliably protected, and the laminate can be made excellent in resistance to piranha solution cleaning. The signal intensity of the above-mentioned metal atoms can be measured as the intensity (atomic %) of the metal atom signal observed from the above-mentioned surface, and is defined as the ratio (%) of the area occupied by the signal of the metal atom in the spectrum obtained by X-ray photoelectron spectroscopy to the total area of all signals.
[0112] The test for evaluating the resistance of the laminate to piranha solution cleaning is a piranha solution cleaning test in which the laminate is immersed in a piranha solution at a temperature of 25°C for 30 minutes. The piranha solution used in the piranha solution cleaning test is a mixture of 98% by mass concentrated sulfuric acid and 30% by mass hydrogen peroxide water in a volume ratio of 4:1. For the laminate with excellent resistance, after the piranha solution cleaning test, no pore-shaped (pinhole-shaped) dissolved sites are generated in the metal-based particle assembly layer 20, or even if such sites exist, the number of such sites is small or the diameter of such sites is small. In addition, for the laminate with excellent resistance, there is a tendency for the surface roughness of the surface of the silicon atom-containing layer 30 (the surface on the opposite side to the substrate 10, the first surface) to change less before and after the piranha solution cleaning test. It should be noted that when the piranha solution cleaning test is performed on a laminate having extremely low resistance to piranha solution cleaning, corrosion may occur to such an extent that the laminate penetrates the metal-based particle assembly layer 20 below the silicon atom-containing layer 30 .
[0113] The silicon-containing atom layer 30 may contain, in addition to silicon (Si) atoms and carbon (C) atoms, oxygen (O) atoms, nitrogen (N) atoms, etc. as atoms that can be identified by X-ray photoelectron spectroscopy. Specific constituent materials of the silicon-containing atom layer 30 include, for example, Si a O b C c 、Si d N e C f 、Si g O h N i C j 、Si k O l 、Si m N n 、Si o O p N q etc., preferably Si a O b C c 、Si d N e C f 、Si g O h N i C j a to q represent the composition ratio of each atom in each compound. The silicon atom-containing layer 30 may be composed of two or more materials. In addition, the silicon atom-containing layer 30 may have a single layer structure or a multilayer structure formed of different materials.
[0114] The signal intensity of oxygen atoms measured by X-ray photoelectron spectroscopy of the first surface 31 of the silicon atom-containing layer 30 is, for example, 30 atomic % or more and 90 atomic % or less. From the viewpoint of improving the resistance of the laminate to piranha solution cleaning, the signal intensity of oxygen atoms is preferably 40 atomic % or more and 80 atomic % or less, more preferably 50 atomic % or more and 70 atomic % or less, further preferably 55 atomic % or more and 65 atomic % or less, and particularly preferably 60 atomic % or more and 65 atomic % or less.
[0115] The signal intensity of silicon atoms measured by X-ray photoelectron spectroscopy of the first surface 31 of the silicon atom-containing layer 30 is, for example, 5 atomic % or more and 50 atomic % or less. From the viewpoint of improving the resistance of the laminate to piranha solution cleaning, the signal intensity of silicon atoms is preferably 10 atomic % or more and 45 atomic % or less, more preferably 20 atomic % or more and 40 atomic % or less, and further preferably 25 atomic % or more and 35 atomic % or less.
[0116] The silicon-atom-containing layer 30 is preferably an amorphous layer. According to the method for manufacturing the laminated body described later, the silicon-atom-containing layer 30 can be made into an amorphous layer even if a heat treatment step is included at a relatively high temperature. The silicon-atom-containing layer 30 is advantageously an amorphous layer in that a material that can be applied to a coating process can be selected as the raw material of the silicon-atom-containing layer 30 and high production volume can be performed industrially.
[0117] The silicon-containing atom layer 30 can be confirmed to be an amorphous layer by X-ray diffraction. That is, when the silicon-containing atom layer 30 is measured by X-ray diffraction according to the conditions described in the [Example] described later, the silicon-containing atom layer 30 can be judged to be an amorphous layer by the absence of a peak having a full width at half maximum (FWHM) of 5° or less derived from a crystal within the range of 2θ=5° to 85° (preferably the range of 0° to 90°).
[0118] The average thickness of the silicon-containing atom layer 30 is usually 10 nm or more and 300 nm or less, preferably 15 nm or more and 250 nm or less, and more preferably 20 nm or more and 200 nm or less. The average thickness of the silicon-containing atom layer 30 may be 30 nm or more, 40 nm or more, 50 nm or more, 55 nm or more, or 60 nm or more. By making the average thickness of the silicon-containing atom layer 30 within the above range, the function of protecting the metal-based particle assembly layer 20 and the durability of the laminate can be fully imparted, and the surface unevenness of the metal-based particle assembly layer 20 can be flattened.
[0119] In addition, if a metal-based particle assembly layer showing the characteristics of [a] and [b] mentioned above is used as the metal-based particle assembly layer 20, even in the case where a silicon atom-containing layer 30 having an average thickness of 10 nm or more is stacked, the function of protecting the metal-based particle assembly layer 20 and the durability of the stacked body can be fully imparted, and the effect of plasma resonance based on the metal-based particle assembly layer 20 (for example, the luminescence enhancement effect of the luminescent body) can be obtained.
[0120] The silicon-atom-containing layer 30 preferably has an average thickness within the above range and has a thickness that covers the entire surface of the metal-based particle assembly layer 20 on the side opposite to the substrate 10. When the silicon-atom-containing layer 30 covers the entire surface of the metal-based particle assembly layer 20 on the side opposite to the substrate 10, it can be confirmed by obtaining a surface image of the stacked body using a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd. or an apparatus equivalent thereto. Alternatively, similarly to the measurement of the signal intensity of carbon atoms on the first surface, the surface of the stacked body on the side opposite to the substrate 10 can be measured by X-ray photoelectron spectroscopy, and the signal intensity of the metal atoms constituting the metal-based particles 21 can be determined to be 2.0 atomic % or less.
[0121] When the silicon atom-containing layer 30 covers the entire surface of the metal-based particle assembly layer 20 on the opposite side to the substrate 10, the signal intensity of the metal atoms constituting the metal-based particles 21 measured by X-ray photoelectron spectroscopy on the surface of the stack on the opposite side to the substrate 10 is preferably 1.5 atomic % or less, more preferably 1.0 atomic % or less, further preferably 0.7 atomic % or less, and particularly preferably below the detection limit.
[0122] The average thickness of the silicon-containing atom layer 30 is measured by the following method. A cross-sectional image of the laminate is obtained using a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd. or an equivalent device. In the obtained cross-sectional image, 10 points on the surface of the metal-based particle assembly layer 20 that form an interface with the silicon-containing atom layer 30 are randomly selected. Then, straight lines are drawn from each of the 10 points to the outer surface (first surface 31) of the silicon-containing atom layer 30 in a manner that is the shortest, and the average value of the lengths of the 10 straight lines obtained is taken as the average thickness of the silicon-containing atom layer 30.
[0123] The silicon-atom-containing layer 30 is preferably a wet coating layer. A wet coating layer refers to a layer formed by a process of applying a coating liquid (a composition for forming a silicon-atom-containing layer described later). When the silicon-atom-containing layer 30 is a wet coating layer, it is advantageous in making the surface of the silicon-atom-containing layer 30 (the surface on the opposite side of the substrate 10, the first surface) smooth. By making the silicon-atom-containing layer 30 a wet coating layer, it is easy to obtain a stacked body having a silicon-atom-containing layer 30 with a small surface roughness (the surface on the opposite side of the substrate 10, the first surface). If the surface roughness of the silicon-atom-containing layer 30 is small, when the surface is subjected to subsequent processing such as coating, it is easy to improve the uniformity of the subsequent processing, and it is also easy to reduce defects caused by the occurrence of defects accompanying the subsequent processing.
[0124] It should be noted that the silicon-containing atom layer 30 can be formed by a vapor deposition method, a sputtering method, a CVD method, etc., but in this case, the obtained silicon-containing atom layer 30 is likely to become a layer having surface irregularities (large surface roughness) following the surface irregularities of the metal-based particle assembly layer 20, and is also likely to become a crystalline silicon-containing atom layer 30.
[0125] The arithmetic mean roughness Ra of the surface of the silicon atom-containing layer 30 (the surface on the opposite side to the substrate 10 side, the first surface) measured in accordance with JISB 0601:2001 is preferably 10 nm or less, more preferably 8 nm or less, further preferably 5 nm or less, further preferably 3 nm or less, and particularly preferably 2 nm or less. Ra (before the test) may be 0.1 nm or more.
[0126] The laminate of the present invention has excellent resistance to piranha solution cleaning. The arithmetic mean roughness Ra of the laminate measured according to JIS B 0601:2001 after the above-mentioned piranha solution cleaning test is preferably 15 nm or less, more preferably 10 nm or less, further preferably 8 nm or less, further preferably 5 nm or less, particularly preferably 3 nm or less, and further particularly preferably 2 nm or less. Ra (after the test) can be 0.1 nm or more.
[0127] For the laminate of the present invention, Ra (before the test) can be less than 10 nm, less than 8 nm, less than 5 nm, less than 3 nm or less than 2 nm, and Ra (after the test) can be less than 10 nm, less than 8 nm, less than 5 nm, less than 3 nm or less than 2 nm. In addition, for the laminate of the present invention, there is a tendency that the surface roughness of the surface of the silicon atom-containing layer 30 (the surface on the opposite side of the substrate 10 side, the first surface) changes little before and after the above test.
[0128] <Sensor element>
[0129] The laminate can be used as a sensor element mounted on a sensor device for detecting a substance to be detected. For example, after the laminate is washed with a piranha solution, a capture substance that specifically binds to the substance to be detected is introduced into a predetermined position on the surface of the silicon atom-containing layer 30 (the surface on the side opposite to the substrate 10, the first surface) by photolithography or the like, thereby forming a sensor element.
[0130] The above-mentioned sensor element can, for example, detect the substance to be detected as follows. Detection can be qualitative detection or quantitative detection, for example, identification or quantification of the substance to be detected. When the labeled substance to be detected that specifically binds to the capture substance possessed by the sensor element is irradiated with excitation light, the marker as the luminophore is excited. Then, the metal-based particle assembly layer of the sensor element, which is preferably a plasma structure, resonates with the excited luminophore, showing enhanced plasma luminescence. The luminescence from the excited luminophore is detected by a detector, so that the substance to be detected can be qualitatively detected or quantitatively detected. For example, by measuring the luminescence intensity, the amount of the substance to be detected can be qualitatively or quantitatively determined.
[0131] According to the sensor element including the laminate of the present invention, the laminate preferably includes a metal-based particle assembly layer which is a plasmon structure. This can exhibit plasmon emission enhancement, thereby improving detection sensitivity and detection accuracy.
[0132] The detected substance is a substance that is the object of qualitative or quantitative detection, and is a substance that specifically binds to the capture substance. There are no particular restrictions on the detected substance, and examples thereof include nucleosides, nucleotides, nucleic acids, proteins, carbohydrates, glycoproteins, lectins, viruses, cells, antibodies, and exogenous bodies. A sensor element in which the detected substance is a substance derived from an organism or a substance related to an organism is also referred to as a biosensor element.
[0133] Nucleic acid refers to a polymer (nucleotide chain) of phosphate esters of nucleosides formed by glycosidic bonds between purine bases or pyrimidine bases and sugars, including oligonucleotides containing probe DNA, polynucleotides, DNA (full length or fragments) polymerized with purine nucleotides and pyrimidine nucleotides, RNA, polyamide nucleotide derivatives (PNA), etc. In addition, nucleosides are compounds formed by glycosidic bonds between bases and sugars, nucleotides are compounds with phosphoric acid bonded to nucleosides, and nucleosides and nucleotides are compounds containing bases.
[0134] The term "specific binding" refers broadly to chemical bonds including non-covalent bonds, covalent bonds, and hydrogen bonds between substances, and examples thereof include interactions between protein molecules and electrostatic interactions between molecules.
[0135] The detection of the captured test substance can be carried out as follows: the test substance is marked in advance with a label as a luminophore, and the luminescence from the label is detected, so that it can be carried out. The label can also be a labeling substance that specifically binds to the complex obtained by the specific binding of the capture substance and the test substance. The luminophore is a substance that emits light by injecting excitation energy based on excitation light. The luminescence principle in the luminophore is not limited, and fluorescence, phosphorescence, chemiluminescence, etc. can be cited. As the luminophore, a substance known in the past can be used.
[0136] The capturing substance is a substance that specifically binds to the substance to be detected and captures it to perform its function. The capturing substance is, for example, fixed on the surface of the silicon-containing atom layer 30. The capturing substance is, for example, a substance having a binding active group that can specifically bind to the substance to be detected. As the binding active group, for example, carboxyl, hydroxyl, etc. that can electrostatically interact with the substance to be detected can be cited. As the capturing substance, there is no particular limitation, for example, nucleosides, nucleotides, nucleic acids, proteins, carbohydrates, glycoproteins, etc. can be cited.
[0137] Examples of sensor devices include biosensor devices such as DNA sequencers, DNA microarrays, virus sensors, ion sensors, microplate readers (protein chips, sugar chain chips, lectin chips, etc.), microspectroscopy devices, and glucose sensors.
[0138] <Method for producing laminate>
[0139] The present invention provides a method for manufacturing a laminate. The laminate is a laminate comprising: a metal-based particle assembly layer composed of a plurality of metal-based particles arranged separately from each other; and a silicon-containing atom layer, the silicon-containing atom layer having a first surface, and the signal intensity of carbon atoms on the first surface measured by X-ray photoelectron spectroscopy is 20.0 atomic % or less. Regarding the specific structure, substrate, metal-based particle assembly layer, metal-based particles, and silicon-containing atom layer of the laminate obtained by the manufacturing method described herein, the description in the above-mentioned <Laminate> is cited. The method for manufacturing a laminate of the present invention is suitable as the method for manufacturing a laminate described in the above-mentioned <Laminate>.
[0140] The method for producing a laminate of the present invention comprises the following steps:
[0141] forming the metal-based particle assembly layer on a substrate;
[0142] A step of coating a silicon atom-containing layer-forming composition on a substrate having a metal-based particle assembly layer formed thereon to form a coating layer; and
[0143] A step of heat-treating the coating layer at a temperature of 300° C. to 800° C.
[0144] The step of forming the metal-based particle assembly layer can be carried out, for example, according to the method for producing the metal-based particle assembly layer described in the above section <Laminated body>.
[0145] In the step of forming the coating layer, the composition for forming the silicon-containing atom layer is applied to the substrate on which the metal-based particle assembly layer is formed. By using such a coating method, a silicon-containing atom layer having a desired average thickness and a smooth surface can be easily formed. Examples of the coating method include spin coating, slit coating, and slit spin coating.
[0146] The composition for forming a silicon-containing atom layer contains: a substance (silicon-containing atom layer forming component) that can form a silicon-containing atom layer, for example, formed from the materials exemplified above, by a process of heat-treating a coating layer. Examples of such substances include spin-on glass (SOG), polysilazane, tetraethyl orthosilicate (TEOS), methyltrimethoxysilane (MTMS) and other silicon-containing substances. Spin-on glass (SOG) has a siloxane structure, and examples thereof include quartz glass, alkylsiloxane polymers, alkylsilsesquioxane polymers, hydrogenated silsesquioxane polymers, hydrogenated alkylsilsesquioxane polymers, and the like.
[0147] Among them, from the viewpoint of forming a silicon-containing atom layer having a signal intensity of carbon atoms that is greater than the above-mentioned preferred lower limit, the composition for forming a silicon-containing atom layer preferably contains a silicon-containing atom layer-forming component having carbon atoms, such as an organic SOG having an organic group or an organic structure. As the organic SOG, SOG having a methyl group or an ethyl group can be cited. By using an organic SOG, the coating property of the composition for forming a silicon-containing atom layer can also be improved.
[0148] The composition for forming a silicon-containing atom layer may further contain a solvent, a reaction catalyst, water, a surfactant, and the like in addition to the silicon-containing atom layer-forming component.
[0149] After the coating layer is formed, a process of heat treating the coating layer at a temperature of 300°C to 800°C is performed. The temperature of the heat treatment is preferably 350°C to 700°C, more preferably 400°C to 650°C, further preferably 450°C to 600°C, and particularly preferably 500°C to 600°C. If the heat treatment temperature is too low, when a silicon-containing atom layer-forming component having carbon atoms is used, the signal intensity of the carbon atoms in the silicon-containing atom layer 30 is likely to become greater than the preferred range. In this case, the resistance of the laminate to piranha solution cleaning becomes low. If the heat treatment temperature is too high, oxidation of the metal-based particle assembly layer 20 is caused, and sometimes the temperature exceeds the decomposition temperature of the oxidized metal-based particles or the melting temperature of the metal-based particle assembly layer. In this case, there is a concern that the metal-based particle assembly layer 20 may be damaged during the heat treatment process.
[0150] The time of heat treatment is, for example, more than 1 minute and less than 720 minutes, preferably more than 2 minutes and less than 480 minutes, more preferably more than 2 minutes and less than 240 minutes. Heat treatment can be carried out in air or inert gas (e.g., nitrogen, argon) atmosphere. The pressure of heat treatment can also be normal pressure.
[0151] The manufacturing method of the laminate may further include a step of degreasing and cleaning the substrate before the step of forming the metal-based particle assembly layer. By further including the step, the resistance of the obtained laminate to piranha solution cleaning can be further improved. As the degreasing and cleaning of the substrate, an appropriate method can be adopted according to the material of the substrate, for example, cleaning using a liquid selected from an organic solvent and water can be cited. As the cleaning method, a method of immersing in the liquid, a method of ultrasonic cleaning while immersing in the liquid, a method of wiping with a cloth (woven fabric, non-woven fabric, etc.) stained with the liquid, etc. can be cited. Degreasing and cleaning can also be a combination of cleaning steps using more than two liquids. For example, when the substrate is a glass substrate, degreasing and cleaning can include, in sequence: ultrasonic cleaning using alcohols (methanol, ethanol, isopropanol, etc.), ultrasonic cleaning using ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.), and ultrasonic cleaning using ultrapure water. Specific embodiments
[0153] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0154] <Example 1>
[0155] (1) Degreasing and cleaning of glass substrates
[0156] A soda glass substrate having a side of 5 cm and a thickness of 0.7 mm was prepared, and the soda glass substrate was cleaned with isopropyl alcohol, cleaned with acetone, and then cleaned with ultrapure water as a degreasing cleaning treatment.
[0157] (2) Formation of Metal-Based Particle Assembly Layer
[0158] Silver particles were grown extremely slowly on a soda glass substrate subjected to a degreasing and cleaning treatment using a DC magnetron sputtering device under the following conditions, thereby forming a metal-based particle assembly layer on the entire surface of the substrate.
[0159] Gas used: Argon
[0160] Chamber pressure (sputtering pressure): 10Pa
[0161] Distance between substrate and target: 100mm
[0162] Sputtering power: 4W
[0163] Average particle size growth rate (average particle size / metal particle growth time): 0.9nm / min
[0164] Average height growth rate (= average deposition rate = average height / metal particle growth time): 0.25nm / min
[0165] Substrate temperature: 300°C
[0166] Metallic particle growth time: 360 minutes
[0167] Figure 2 This is a SEM image of the metal-based particle assembly layer formed on the substrate observed from directly above. Figure 2 (a) is a magnified image with a scale of 10,000 times. Figure 2 (b) is a magnified image at a scale of 50,000. The SEM image was obtained using a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd.
[0168] according to Figure 2 The SEM image shown in FIG. 1 shows that the average particle size of the silver particles constituting the metal-based particle assembly layer is 335 nm, the average inter-particle distance is 16.7 nm, and the standard deviation of the average inter-particle distance is 27.8 nm. The SEM image shows that the metal-based particle assembly layer has a particle size of about 6.25×10 10 (about 25 / μm 2 ) silver particles. In addition, based on the results of AFM imaging using KEYENCE CORPORATION's "VN-8010", the average height of the silver particles was found to be 96.2 nm. From this, the aspect ratio (average particle diameter / average height) of the silver particles was calculated to be 3.48. The AFM image of the metal-based particle assembly layer is shown in Figure 3 . Figure 3 The size of the images shown is 5 μm×5 μm.
[0169] A tester [multimeter ("E2378A" manufactured by Hewlett-Packard Development Company, LP) was connected to the surface of the metal-based particle assembly layer formed on the substrate to check the conductivity. As a result, it was confirmed that the metal-based particle assembly layer had no conductivity.
[0170] (3) Formation of silicon-containing atomic layer
[0171] The silicon-containing atom layer-forming composition is spin-coated on the metal-based particle assembly layer formed on the substrate to form a coating layer. Next, an intermediate laminate consisting of substrate / metal-based particle assembly layer / coating layer is introduced into a drying furnace and heat-treated at 550° C. for 30 minutes in air at normal pressure to obtain a substrate / metal-based particle assembly layer / silicon-containing atom layer-forming intermediate laminate. Figure 1 As the composition for forming the silicon-containing atom layer, a composition prepared by diluting "OCD T-7 5500T" manufactured by Tokyo Ohka Kogyo Co., Ltd., which is an organic SOG material, with ethanol was used.
[0172] (4) Analysis of silicon-containing atomic layers and evaluation of laminates
[0173] (4-1) Covering state of the metal-based particle assembly layer based on the silicon-containing atomic layer and the average thickness of the silicon-containing atomic layer
[0174] The laminate was cut along a plane parallel to the stacking direction of the layers, and a cross-sectional image of the cut portion was observed using a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd., thereby confirming that the silicon-atom-containing layer covered the entire surface of the metal-based particle assembly layer on the side opposite to the glass substrate. In addition, the surface of the laminate on the side opposite to the glass substrate was measured by X-ray photoelectron spectroscopy according to the apparatus and measurement conditions described later, and as a result, no signal of silver atoms was detected. Therefore, from this point of view, it was also confirmed that the silicon-atom-containing layer covered the entire surface of the metal-based particle assembly layer on the side opposite to the glass substrate. In addition, it was confirmed that the silicon-atom-containing layer was formed not only on the surface of the silver particles in the metal-based particle assembly layer, but also in the gaps between the silver particles.
[0175] The average thickness of the silicon atom-containing layer measured by the above-mentioned measurement method using a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd. was 87.0 nm.
[0176] (4-2) Signal intensity of atoms constituting the first surface
[0177] By X-ray photoelectron spectroscopy under the following measuring conditions using the following device, the intensity (atomic %) of the atomic signal observed from the first surface (the surface on the opposite side of the glass substrate in the laminate) containing the silicon atom layer is obtained. The signal intensity of each atom is defined as the ratio (%) of the area occupied by the signal of each atom in the spectrum obtained by X-ray photoelectron spectroscopy in the total area of all signals. For any three parts of the first surface, the ratio (%) of the area of the signal of each atom is measured, and the average value of their measured values is used as the intensity of the atomic signal. The atoms identified by X-ray photoelectron spectroscopy are C, O and Si. These signal intensities are shown below.
[0178] C: 8.8 atomic%
[0179] O: 61.9 atomic %
[0180] Si: 29.3 atomic%
[0181] (Equipment and measurement conditions)
[0182] · Equipment: K-Alpha X-ray Photoelectron Spectroscopy System manufactured by Thermo Fisher Scientific Inc.
[0183] Measuring range: 400×800mm
[0184] · Measured elements (accumulated times): O(4), C(4), Si(4)
[0185] Dwell Time: 50ms
[0186] Neutralizing gun: Yes
[0187] GCIB: Yes (for removing surface contamination)
[0188] (4-3) Crystal state containing silicon atomic layer
[0189] The XRD spectrum of the first surface (the surface on the opposite side of the glass substrate in the laminate) of the silicon-containing atom layer was obtained by X-ray diffraction under the following measurement conditions using the following apparatus. There was no peak with a full width at half maximum (FWHM) of 5° or less in the entire range of 2θ, thus confirming that the silicon-containing atom layer was an amorphous layer.
[0190] (Equipment and measurement conditions)
[0191] · Device: SmartLab manufactured by Rigaku Corporation
[0192] ·Measurement method: θ / 2θ measurement method
[0193] ·Measurement range: 2θ=5°~90°
[0194] Tube voltage: 45kV
[0195] Tube current: 200mA
[0196] (4-4) Arithmetic mean roughness Ra of the first surface (before test)
[0197] The arithmetic mean roughness Ra of the first surface of the silicon atom-containing layer in the obtained laminate was measured in accordance with JIS B 0601:2001 and was found to be 1.5 nm.
[0198] (4-5) Arithmetic mean roughness Ra of the first surface (after test)
[0199] The obtained laminate was subjected to a piranha solution cleaning test in which the laminate was immersed in a piranha solution at a temperature of 25° C. for 30 minutes. The piranha solution used was a mixed solution prepared by mixing 98% by mass concentrated sulfuric acid and 30% by mass hydrogen peroxide water at a volume ratio of 4:1. After the test, the arithmetic mean roughness Ra was measured at any one point of the first surface measured in accordance with JIS B 0601:2001 in the same manner as in the above (4-4), and the result was 2.0 nm.
[0200] (4-6) Evaluation of Laminated Body's Resistance to Piranha Solution Cleaning
[0201] The first surface of the silicon atom-containing layer in the laminate after the piranha solution cleaning test described in (4-5) above was observed with an optical microscope. The surface properties were found to be the same as before the test.
[0202] <Example 2>
[0203] A substrate / metal-based particle assembly layer / silicon-containing atom layer was obtained in the same manner as in Example 1 except that the temperature of the heat treatment performed after forming the coating layer of the silicon-containing atom layer-forming composition was 400°C. Figure 1 The obtained laminate was subjected to analysis of the silicon atom-containing layer and evaluation of the laminate in the same manner as in Example 1 (4).
[0204] In this embodiment, both observation of cross-sectional images using a scanning electron microscope "JSM-5500" and measurement based on X-ray photoelectron spectroscopy confirmed that the silicon-containing atom layer covered the entire surface of the metal-based particle assembly layer on the side opposite to the glass substrate. The average thickness of the silicon-containing atom layer was 138.1 nm.
[0205] The first surface of the silicon atom-containing layer was measured by X-ray photoelectron spectroscopy, and as a result, atoms were identified as C, O, Si, and Ag. The signal intensities of these atoms are shown below.
[0206] C: 11.7 atomic %
[0207] O: 58.4 atomic%
[0208] Si: 29.1 atomic%
[0209] Ag: 0.8 atomic%
[0210] From the XRD spectrum of the first surface of the silicon atomic containing layer, it was confirmed that the silicon atomic containing layer was an amorphous layer.
[0211] The arithmetic mean roughness Ra (before the test) of the first surface of the silicon atom-containing layer was measured, and the result was 2.1 nm. In addition, the arithmetic mean roughness Ra (after the test) of the first surface was measured, and the result was 4.0 nm. The first surface of the silicon atom-containing layer in the laminate after the piranha solution cleaning test was observed with an optical microscope, and the result confirmed that extremely small pore-shaped dissolved sites were slightly generated.
[0212] <Example 3>
[0213] A substrate / metal-based particle assembly layer / silicon-containing atom layer was obtained in the same manner as in Example 2 except that the glass substrate was not degreased and cleaned. Figure 1 The obtained laminate was subjected to analysis of the silicon atom-containing layer and evaluation of the laminate in the same manner as in Example 1 (4).
[0214] In this embodiment, both observation of cross-sectional images using a scanning electron microscope "JSM-5500" and measurement based on X-ray photoelectron spectroscopy confirmed that the silicon-containing atom layer covered the entire surface of the metal-based particle assembly layer on the side opposite to the glass substrate. The average thickness of the silicon-containing atom layer was 138.1 nm.
[0215] The first surface of the silicon atom-containing layer was measured by X-ray photoelectron spectroscopy, and as a result, atoms were identified as C, O, Si, and Ag. The signal intensities of these atoms are shown below.
[0216] C: 10.1 atomic%
[0217] O: 59.6 atomic%
[0218] Si: 29.2 atomic%
[0219] Ag: 1.1 atomic%
[0220] From the XRD spectrum of the first surface of the silicon atomic containing layer, it was confirmed that the silicon atomic containing layer was an amorphous layer.
[0221] The arithmetic mean roughness Ra (before the test) of the first surface of the silicon atom-containing layer was measured, and the result was 2.1 nm. In addition, the arithmetic mean roughness Ra (after the test) of the first surface was measured, and the result was 13.3 nm. The first surface of the silicon atom-containing layer in the laminate after the piranha solution cleaning test was observed with an optical microscope, and the result confirmed that a small pore-like dissolved site was slightly generated.
[0222] <Comparative Example 1>
[0223] A substrate / metal-based particle assembly layer / silicon-containing atom layer-forming composite material was obtained in the same manner as in Example 1 except that the glass substrate was not degreased and the temperature of the heat treatment after forming the coating layer of the silicon-containing atom layer-forming composition was set to 200°C. Figure 1 The obtained laminate was subjected to analysis of the silicon atom-containing layer and evaluation of the laminate in the same manner as in Example 1 (4).
[0224] In this comparative example, both observation of cross-sectional images using a scanning electron microscope "JSM-5500" and measurement based on X-ray photoelectron spectroscopy confirmed that the silicon-containing atom layer covered the entire surface of the metal-based particle assembly layer on the side opposite to the glass substrate. The average thickness of the silicon-containing atom layer was 142.2 nm.
[0225] The first surface of the silicon atom-containing layer was measured by X-ray photoelectron spectroscopy. As a result, the atoms identified were C, O and Si, and their signal intensities were as follows.
[0226] C: 20.7 atomic%
[0227] O: 51.5 atomic%
[0228] Si: 27.8 atomic%
[0229] From the XRD spectrum of the first surface of the silicon atomic containing layer, it was confirmed that the silicon atomic containing layer was an amorphous layer.
[0230] The arithmetic mean roughness Ra (before the test) of the first surface of the silicon-containing atomic layer was measured and found to be 1.5 nm. The first surface of the silicon-containing atomic layer in the laminate after the piranha solution cleaning test was observed using an optical microscope, and the results showed that there were areas where the silicon-containing atomic layer disappeared due to dissolution, and the metal-based particle assembly layer thereunder also disappeared due to dissolution.
[0231] Figure 4 This is a SEM image of the laminate of Example 1 before the piranha solution cleaning test when observed from the silicon-containing atomic layer side. Figure 5 The SEM images of the laminate of Example 1 after the piranha solution cleaning test are observed from the silicon-containing layer side. All are magnified images at a scale of 50,000 times. The SEM images were obtained using a scanning electron microscope "JSM-5500" manufactured by JEOL Ltd. It can be confirmed that there is basically no change in the surface properties before and after the piranha solution cleaning test.
[0232] in addition, Figure 6 to Figure 10 Each is an optical microscope photograph (magnification 700) of the following stacked body observed from the silicon atom-containing layer side.
[0233] Figure 6: Laminated body of Example 1 before the piranha solution cleaning test
[0234] Figure 7 : Laminated body of Example 1 after piranha solution cleaning test
[0235] Figure 8 : Laminated body of Example 2 after piranha solution cleaning test
[0236] Fig. 9 : Laminated body of Example 3 after piranha solution cleaning test
[0237] Fig.10 : Laminated body of Comparative Example 1 after piranha solution cleaning test
[0238] Description of Reference Numerals
[0239] 10 substrate, 20 metal-based particle assembly layer, 21 metal-based particles, 30 silicon-atom-containing layer, 31 first surface.
Claims
1. A laminate comprising: a metal-based particle assembly layer composed of a plurality of metal-based particles arranged separately from each other; and a silicon-containing atom layer, The silicon-atom-containing layer has a first surface, The signal intensity of carbon atoms on the first surface measured by X-ray photoelectron spectroscopy is 20.0 atomic % or less.
2. The laminate according to claim 1, comprising: a substrate; the metal-based particle assembly layer disposed on a surface of the substrate; and the silicon-containing atom layer disposed on the metal-based particle assembly layer. The silicon atom-containing layer is disposed so as to cover the entire surface of the metal-based particle assembly layer on the side opposite to the substrate.
3. The laminate according to claim 1 or 2, wherein: The silicon-atom-containing layer is an amorphous layer.
4. The laminate according to claim 1 or 2, wherein: The silicon-atom-containing layer is a wet coating layer.
5. The laminate according to claim 1 or 2, wherein: The average thickness of the silicon atom-containing layer is greater than or equal to 10 nm and less than or equal to 300 nm.
6. The laminate according to claim 1 or 2, wherein: The metal-based particles are formed of silver.
7. The laminate according to claim 1 or 2, wherein: The plurality of metal-based particles have an average particle size in the range of 200 nm to 1600 nm, an average height in the range of 55 nm to 500 nm, and an aspect ratio defined by a ratio of the average particle size to the average height in the range of 1 to 8. In the metal-based particle assembly layer, the plurality of metal-based particles are arranged such that an average distance between each of the metal-based particles adjacent thereto is within a range of 1 nm to 150 nm.
8. The laminate according to claim 7, wherein: The aspect ratio is greater than 1. 9 . The laminate according to claim 1 , wherein the first surface has an arithmetic mean roughness Ra of 10 nm or less as measured in accordance with JIS B 0601:2001.
10. The laminate according to claim 1 or 2, wherein the first surface has an arithmetic mean roughness Ra of 15 nm or less measured in accordance with JIS B 0601:2001 after being immersed in a mixed solution of 98% by mass concentrated sulfuric acid and 30% by mass hydrogen peroxide water at a volume ratio of 4:1 at a temperature of 25°C for 30 minutes.
11. A method for producing a laminate, wherein: The laminate comprises: a metal-based particle assembly layer composed of a plurality of metal-based particles arranged separately from each other; and a silicon-containing atom layer. The silicon-atom-containing layer has a first surface, The signal intensity of carbon atoms on the first surface measured by X-ray photoelectron spectroscopy is 20.0 atomic % or less, The manufacturing method comprises the following steps: forming the metal-based particle assembly layer on a substrate; A step of coating a silicon atom-containing layer-forming composition on a substrate having the metal-based particle assembly layer formed thereon to form a coating layer; and A step of heat treating the coating layer at a temperature of 300° C. to 800° C.
12. The manufacturing method according to claim 11, wherein: Before the step of forming the metal-based particle assembly layer, the method further includes the step of degreasing and cleaning the substrate.
Citation Information
Patent Citations
Photochemical fluorescent sensor and measuring method thereof
JP1996271431A
Metallic particle assembly
CN104620393A
Method for producing polarizing element
JP2013182262A
Gas barrier film, transparent conductive member, and organic electroluminescent element
JP2017077684A
Electron emission element, manufacturing method therefor, and manufacturing method for electronic element
JP2019050140A